Lack of effect of antiviral therapy in nondividing hepatocyte cultures on the closed circular DNA of woodchuck hepatitis virus. - Moraleda, G (1997)
The template for synthesis of hepadnaviral RNAs is a covalently closed circular (ccc) DNA located in the nucleus of the infected hepatocyte. Hepatocytes are normally long-lived and nondividing, and antiviral therapies in chronically infected individuals face the problem of eliminating not only the replicative forms of viral DNA found in the cytoplasm but also the cccDNA from the nucleus. Because cccDNA does not replicate semiconservatively, it is not an obvious target for antiviral therapy. However, elimination of cccDNA might be facilitated if its half-life were short in comparison to the generation time of hepatocytes and if new cccDNA formation were effectively blocked. We have therefore measured cccDNA levels in woodchuck hepatocyte cultures following in vitro infection with woodchuck hepatitis virus and treatment with inhibitors of viral DNA synthesis. The viral reverse transcriptase inhibitors lamivudine (3TC) [(-)-beta-L-2',3'-dideoxy-3'-thiacytidine), FTC (5-fluoro-2',3'-dideoxy-3'-thiacytidine) and ddC (2',3'-dideoxycytidine) were added to the cultures beginning at 4 days postinfection. Treatment for up to 36 days with 3TC reduced the amount of cccDNA in the cultures not more than twofold compared to that of an untreated control. Treatment with ddC for 36 days and with FTC for 12 days resulted in effects similar to that of treatment with 3TC. Moreover, the declines in cccDNA appeared to reflect the loss of hepatocytes from the cultures rather than of cccDNA from hepatocytes. These results emphasize the important role of the longevity of the infected hepatocytes in the persistence of an infection.